2023
DOI: 10.3389/ffgc.2023.1099558
|View full text |Cite
|
Sign up to set email alerts
|

Strict forest protection: A meaningful contribution to Climate-Smart Forestry? An evaluation of temporal trends in the carbon balance of unmanaged forests in Germany

Abstract: The role of unmanaged forests is discussed controversially in the context of climate change. One of the key questions is, whether they can contribute to the mitigation of climate change as a carbon sink and storage. However, carbon dynamics of forests after the cessation of management are not well understood. We analyzed a set of 64 forest sites, covering wide gradients of time since abandonment (0–68 years) and stand age (65–261 years) in even-aged, unmanaged beech forests. Five sites that were unmanaged for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 83 publications
(110 reference statements)
0
13
0
Order By: Relevance
“…All these objectives are well substantiated in the context of Czech forestry, where soil remains notably disturbed [ 29 , 30 ] and the average amount of deadwood remains low [ 31 ]. Hence, increasing the carbon pool of dead organic matter and indirectly soil represents—at least for medium term [ 32 ]—additional mitigation potential, besides enhancing biodiversity, for forests that have been intensively managed earlier.…”
Section: Discussionmentioning
confidence: 99%
“…All these objectives are well substantiated in the context of Czech forestry, where soil remains notably disturbed [ 29 , 30 ] and the average amount of deadwood remains low [ 31 ]. Hence, increasing the carbon pool of dead organic matter and indirectly soil represents—at least for medium term [ 32 ]—additional mitigation potential, besides enhancing biodiversity, for forests that have been intensively managed earlier.…”
Section: Discussionmentioning
confidence: 99%
“…The studied set-aside forests appeared to be still below the ecosystem's carbon carrying capacity: the carbon stock change rates were not lower for plots with high initial carbon stocks (no clear trend in Figure 3), indicating that the carbon accumulation did not yet slow down and the carbon stock continued to increase in forests that already built up a large carbon stock over time. Studies in German set-aside forests indeed indicated that the in situ carbon sequestration-and hence additionality of setting aside forests-remains high during at least the first 50 years after set aside, before they approach their ecological carrying capacity and related dynamic steady-state level Nagel et al, 2023).…”
Section: Additionality Of Set-aside Forestsmentioning
confidence: 99%
“…In regions with a long history of intensive forest management and no remaining primary forests (e.g., north-western or central Europe), the aboveground carbon stock in forests is expected to be distinctively lower than the natural ecosystem carbon carrying capacity Nagel et al, 2023). Forests in these regions thus represent a high potential for carbon storage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Permanent set-aside and the associated abandonment of management by harvesting beeches from age 100 until the end of their life initially has a positive effect on the annual CO2 removal potential of about 14-16 t CO2 ha -1 a -1 assuming today's set-aside beech stands of the age classes 120, 140 and 160 years in the public forest if no calamities occur (Bolte et al 2022; Figure 3h). However, after a certain time since abandonment, the culmination is reached as the additional growth potential is exhausted, the removal potential decreases, and beginning decay can also reduce the carbon stocks accumulated until that time (according to Nagel et al 2023, this occurs around 50 years after abandonment). In the case of temporary set-aside over a period of 25 years, for example, the further development will depend on whether and in what way management is resumed.…”
Section: Co2 Removal Dynamicsmentioning
confidence: 99%